Laboratory Studies on Compressive Strength of Normal Concrete Using Coral Limestone on Timor Island, East Nusa Tenggara Province as a Substitute for Coarse Aggregate - Alfa Y Lukas (Universitas Pancasakti Tegal, 2024)
Coral limestones are called the people of East Nusa Tenggara as Batu Karang, scattered almost all over the island of Timor, especially in the western part of the island of Timor but are not used properly. The use of coral limestone in the building construction industry in East Nusa Tenggara is limited as a filling material for foundation and floor work but has not been used as a structural or non-structural concrete constituent material. Based on these conditions, it is necessary to research the use of coral limestone as a substitute for coarse aggregate so that it can be used as an alternative material for structural and non-structural concrete which is applied to simple house construction. The research method was an experiment on 48 samples with a maximum size of 40 mm coral limestone, and a maximum size of coarse aggregate (gravel) of 20 – 30 mm, variations of coral limestone as a substitute for gravel were 0%, 5%, 25%, 50%. Each variation consists of 12 cylindrical samples with a diameter of 15 cm and a height of 30 cm, while the target quality, fc' = 30 MPa, and the planned age of observation are 7, 14, and 28 days. The test results showed an increase in the compressive strength of concrete from the age of 7 to 28 days. For the 0% variation, the increase was 21,31% and the 5%, 25% and 50% variation were 27,18%, 23.63% and 23,44%, respectively. While the increase was more significant in the 25% variation, which increased by 11,66% with the concrete compressive strength value of 33,37 Mpa at the age of 28 days, and in the 50% variation, the concrete compressive strength decreased by 1,25% with the compressive strength value of 29,51 Mpa. This study concludes that coral reefs on the island of Timor, especially the West Kupang area can be used as an alternative material for structural concrete and non-structural concrete to support infrastructure in the province of East Nusa Tenggara.